Automated launch system for a tunnel inspection robot - Gui, Celine Si Ying (Nanyang Technological University, 2021)
A clean sanitary water system is vital for every country’s continual progress. Singapore has invested and spent considerable amount of effort in its sanitary system – the Deep Tunnel Sewage System (DTSS), which began as early as the 1990s. Serving a current population of close to 6 million, about 595 million cubic metres (m^3) of used water, equivalent to 238,000 Olympic-size swimming pools is treated through Singapore’s treatment system. The ongoing project thus requires constant building and maintenance of the sewage tunnels in order to ensure the system is able to operate smoothly amongst the upgrading, in addition to the growing population.